Prevalence of burnout and its associated factors among healthcare providers in government health clinic in Kuantan, Pahang during Covid 19 pandemic - Tg Arif @ Tg Zainuddin, Tg Putri Syarizan; Said, Abdul Hadi; Yusof, Muhammad Zubir (2023)
Burnout is defined as psychological syndrome of emotional exhaustion, depersonalization, and reduced personal accomplishment that can occur among individuals who work with other people in some capacity, especially in demanding job like healthcare profesionals1 . • High level of burnout among healthcare providers has been associated with decreased work efficiency2 . • The aim of this study was to identify the extent of burnout among them and to identify its associated factors.